2020
DOI: 10.1002/ijgo.13135
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for gastroschisis: A case–control study in a Brazilian population

Abstract: Objective: To evaluate risk factors associated with fetal gastroschisis.Methods: As a secondary aim of a larger case-control study, pregnant women attending the Fetal Medicine Unit at the Department of Obstetrics and Gynecology at Hospital das Clinicas, Sao Paulo University Medical School between July 1, 2013, and July 31, 2015, were allocated into either the gastroschisis group, where the woman was carrying a fetus with gastroschisis, or the control group, where the fetus was normal. Patients in the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…For this methylation study, we used the mother-infant pairs from the previously described case-control study to investigate nutrition and other risk factors in gastroschisis. 8,28,29 The patients were treated, blood was drawn, and data were collected at the Departamento de Obstetrícia e Ginecologia do Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo between July 2013 and July 2015. Briefly, consenting singleton pregnant women at gestational age under 34 weeks and with isolated fetal gastroschisis were included in this study.…”
Section: Techniques and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this methylation study, we used the mother-infant pairs from the previously described case-control study to investigate nutrition and other risk factors in gastroschisis. 8,28,29 The patients were treated, blood was drawn, and data were collected at the Departamento de Obstetrícia e Ginecologia do Hospital das Clínicas, Faculdade de Medicina da Universidade de São Paulo between July 2013 and July 2015. Briefly, consenting singleton pregnant women at gestational age under 34 weeks and with isolated fetal gastroschisis were included in this study.…”
Section: Techniques and Materialsmentioning
confidence: 99%
“…[4][5][6] A likely explanation is the association with risk factor-related life habits, and these are mainly smoking, regular alcohol consumption, and genitourinary tract infections. [7][8][9] Family history is also evidence of a genetic contribution associated with gastroschisis, and the recurrence risk lies between 2.4% and 6.9%. 10,11 However, genetic studies are still controversial and have been unable to provide enough data on the etiopathology of gastroschisis (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The existing literature generallyalthough not universally [9][10][11] -supports the hypothesis that periconceptional alcohol consumption is associated with increased risk of gastroschisis. [12][13][14][15][16][17] However, previous studies were limited in their ability to assess effects of different levels of alcohol intake (i.e. binge drinking) or joint effects with other factors strongly associated with gastroschisis, such as maternal age.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…However one age-matched case-control study in Brazil used a modified version of the NBDPS questionnaire and reported a moderately strong association between periconceptional alcohol consumption and gastroschisis (OR 2.6) 16. That this estimate is higher than among NBDPS participants may reflect different consumption patterns be-…”
mentioning
confidence: 99%